2018
DOI: 10.1111/micc.12486
|View full text |Cite
|
Sign up to set email alerts
|

Differential arterial and venous endothelial redox responses to oxidative stress

Abstract: Arterial and venous endothelial cells exhibit differential responses to oxidant stress, and decreases in GSH:GSSG are more exacerbated in venous endothelial cells. Specific pathogenesis in these vascular conduits, with respect to oxidant stress handling, warrants further study, especially considering surgical interventions such as Coronary artery bypass grafting that use both interchangeably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
(47 reference statements)
2
10
0
1
Order By: Relevance
“…Despite the luminal narrowing, a truly obstructive small vessel disease does not seem to be a relevant feature 5,22 . Importantly, previous work showed that the abnormal intramural small vessels closely co‐localize to the fibrotic scars 16 . Intramural small coronary arteries abnormalities consist mainly in medial hypertrophy, intimal proliferation, perimysial and intra‐arterial fibrosis, found in the interventricular septum.…”
Section: Coronary Microvascular Dysfunction In Hypertrophic Cardiomyomentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the luminal narrowing, a truly obstructive small vessel disease does not seem to be a relevant feature 5,22 . Importantly, previous work showed that the abnormal intramural small vessels closely co‐localize to the fibrotic scars 16 . Intramural small coronary arteries abnormalities consist mainly in medial hypertrophy, intimal proliferation, perimysial and intra‐arterial fibrosis, found in the interventricular septum.…”
Section: Coronary Microvascular Dysfunction In Hypertrophic Cardiomyomentioning
confidence: 98%
“…H 2 O 2 produced within mitochondria diffuses to the cytosol and sarcolemma, reaching extracellular space and leading to dilatation of vascular smooth muscle 15 . So, oxidative stress constitutes an important contributor to endothelial dysfunction, which culminates in the loss of endothelial‐dependent vasodilation and an increase in inflammation‐mediated cellular adhesion to the endothelium 16 . Furthermore, the presence of comorbidities that increase oxidative stress constitutes a further contributor to microvascular dysfunction.…”
Section: Coronary Physiologymentioning
confidence: 99%
“…Recently, Shrestha et al [23] reported that VECs are more susceptible to the oxidative stress than AECs. These data support the opinion that oxidative stress plays a major role in the dysfunction of endothelial cells in patients treated with hemodialysis [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, veins, especially postcapillary venules, are the main sites of leukocyte chemotaxis during inflammation [ 184 , 186 ]. In the oxidative stress response, the venous endothelium showed a significant increase in inflammation and a decrease in proliferative phenotype [ 187 ].…”
Section: Heterogeneity Of Vascular Endotheliummentioning
confidence: 99%